Optimization of the Estrus Synchronization Method and its Effect on Bulk Tank Milk Somatic Cell Count in Dairy Cattle Farming - Saat, Nevzat; Risvanli, Ali; Seker, Ibrahim; Kaygusuzoglu, Erdal; Koseman, Abdurrahman (Friends Science Publ, 2017)
Effect of various estrus synchronization methods on bulk tank milk somatic cell count (BTMSCC) was investigated. One-hundred Simmental cows within a single dairy farm were randomized into four equal groups: no treatment (Group 1, control group); application of a progesterone-releasing intravaginal device (Group 2); administration of double-dose prostaglandin F-2 alpha (PGF(2)-alpha) with an 11-day interval (Group 3); and subjected to the Ovsynch protocol (Group 4). Bulk tank milk (BTM) samples were collected daily for one month and BTMSCCs calculated. Progesterone and estradiol concentrations were also measured at 3-day intervals. BTMSCC of the Ovsynch protocol group was not significantly different from that of the control group, suggestive of good udder health. Based on this finding, we propose that spontaneous estrus and the Ovsynch protocol are preferable methods for estrus synchronization than progesterone-releasing intravaginal device (PRID) and PGF(2)-alpha approaches. (C) 2017 Friends Science Publishers
Keywords: Estrus synchronization; Bulk tank milk; Somatic cell count; Dairy